2019
DOI: 10.1053/j.gastro.2019.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Targeted Genome Profile Analysis of Pancreatic Ductal Adenocarcinomas Identifies Genetic Alterations That Might Be Targeted With Existing Drugs or Used as Biomarkers

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e19 (https://www. gastrojournal.org/cme/home). Learning Objective: Upon completion of this CME activity, successful leaners will be able to identify current clinically relevant genomic alterations in pancreatic ductal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
228
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(279 citation statements)
references
References 59 publications
17
228
7
Order By: Relevance
“…Singhi et al also reported results from NGS of a large PDAC cohort (3594 cases): interestingly, one case among the three detected MSI/dMMR PDACs harboured the druggable FGFR2-POC1B fusion. 44 Regarding the presence of any potential specific driver genes in MSI/dMMR PDAC, we found a bi-univocal correspondence regarding genes belonging to the JAK/STAT pathway and those of KMT2 family. Indeed, these have been described as frequently mutated in MSI/dMMR cancers of different extrapancreatic sites 45 46 ; the review of all molecular data of MSI/ dMMR PDAC showed the involvement of the JAK/STAT pathway also in MSI/dMMR PDAC, given that the paper by Wartenberg et al, 39 reported a higher mutation rate of JAK3 specifically in this genetic subgroup (3/5 MSI/dMMR cases vs 4/105 microsatellite-stable PDAC, p<0.01, Fisher's exact test; all these cases were KRAS mutated), and in the paper by Singhi et al, two of the three reported MSI/dMMR PDAC harboured a JAK1 mutation (2/3 MSI/dMMR PDAC vs 0/608 microsatellitestable PDAC with actionable targets, p<0.01, Fisher's exact test).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Singhi et al also reported results from NGS of a large PDAC cohort (3594 cases): interestingly, one case among the three detected MSI/dMMR PDACs harboured the druggable FGFR2-POC1B fusion. 44 Regarding the presence of any potential specific driver genes in MSI/dMMR PDAC, we found a bi-univocal correspondence regarding genes belonging to the JAK/STAT pathway and those of KMT2 family. Indeed, these have been described as frequently mutated in MSI/dMMR cancers of different extrapancreatic sites 45 46 ; the review of all molecular data of MSI/ dMMR PDAC showed the involvement of the JAK/STAT pathway also in MSI/dMMR PDAC, given that the paper by Wartenberg et al, 39 reported a higher mutation rate of JAK3 specifically in this genetic subgroup (3/5 MSI/dMMR cases vs 4/105 microsatellite-stable PDAC, p<0.01, Fisher's exact test; all these cases were KRAS mutated), and in the paper by Singhi et al, two of the three reported MSI/dMMR PDAC harboured a JAK1 mutation (2/3 MSI/dMMR PDAC vs 0/608 microsatellitestable PDAC with actionable targets, p<0.01, Fisher's exact test).…”
Section: Resultsmentioning
confidence: 66%
“…Indeed, these have been described as frequently mutated in MSI/dMMR cancers of different extrapancreatic sites 45 46 ; the review of all molecular data of MSI/ dMMR PDAC showed the involvement of the JAK/STAT pathway also in MSI/dMMR PDAC, given that the paper by Wartenberg et al, 39 reported a higher mutation rate of JAK3 specifically in this genetic subgroup (3/5 MSI/dMMR cases vs 4/105 microsatellite-stable PDAC, p<0.01, Fisher's exact test; all these cases were KRAS mutated), and in the paper by Singhi et al, two of the three reported MSI/dMMR PDAC harboured a JAK1 mutation (2/3 MSI/dMMR PDAC vs 0/608 microsatellitestable PDAC with actionable targets, p<0.01, Fisher's exact test). 44 Furthermore, we found that alterations affecting the KMT2 family were involved as well, since 3/3 MSI/dMMR cases described by Singhi et al harboured KMT2 mutations (two cases with KMT2D and one case KMT2C mutation; 3/3 KMT2 mutated MSI/dMMR PDAC vs 32/608 KMT2 mutated microsatellite-stable PDAC with actionable targets, p<0.01, Fisher's exact test; the MSI/dMMR and KMT2 mutated cases were KRAS wild type).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, frequencies of MSI-high tumors of more than 10% were reported in small studies. In a study with a large number of patients (n = 3954) [27], MSI-high pancreatic cancer was found in very few patients (0.5%). In a study that targeted 12,019 patients with 32 types of cancer, the rate of MSI-high tumors was less than 2% in pancreatic cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…In past reports, the frequency of MSI-high tumors was 0-29% in pancreatic cancer [25][26][27][28][29][30]. However, frequencies of MSI-high tumors of more than 10% were reported in small studies.…”
Section: Discussionmentioning
confidence: 99%